Alat Pendeteksi Denyut Nadi Berbasis Arduino Yang Diinterfacekan Ke Komputer - eko sulistyo (Manutech : Jurnal Teknologi Manufaktur, 2016)
Heartbeat/pulse is an important factor in the health sector that determines the health condition ofa person's body. The method of measuring the number of the pulses is still using the manual method bycalculating the rate of the heartbeat/pulse per minute. To know one's pulse, it needs to makemeasurements in the hospital, so not everyone can measure their own pulse. The solution of this problemis the manufacture of human pulse detection device that works automatically in real time and can beconnected with the computer. The purpose of this study is to help people or medical personnel incalculating the pulse rate digitally. The stages of this research is the pulse sensor used to detect thehuman pulse can be put on a three-site measurements, on a finger, ear and forehead, then processed bythe arduino mega 2560 as the central system. The measurement data is Beat Per Minute (BPM) will beshown to the LCD and can be also interfaced into a database using Visual Basic 6.0. The result shows thatthe average pulse measurement by using the tool is 77.3 BPM (Beat Per Minute) and manually is 76 BPM(Beat Per Minute) with the accuracy of this tool reaches 98.32% and it takes 10 seconds to display theaverage value of BPM (Beat Per Minute).